Assessment of Digital Literacy Skills for Supporting Off-Campus Teaching at Selected University Libraries in Kenya - Masinza, Faith Lugulu; Gichohi, Paul Maku; Nzioka, Catherine Mueni (International Journal of Professional Practice, 2022)
University libraries in Kenya are deficiently prepared to launch and operationalize full-fledged off-campus information products and services; hence, the wavering support for off-campus learning and teaching. The purpose of this study was to assess the digital literacy skills of selected university libraries in supporting off-campus teaching. The study was anchored on the technological pedagogical content knowledge model. Data was obtained from Kenyatta, Nairobi and Kenya College of Accountancy universities. A descriptive survey research design was employed and the target population was 127 university library staff and 491 faculty members from business, education, information technology, and graduate studies departments. Census of all the library staff was done, while a sample size of 220 faculty members was obtained using a stratified sampling technique. A semi structured questionnaire was used to collect the data. Validity and reliability tests were conducted on the data instrument. Data was analyzed using descriptive statistics, correlation and thematic analysis. The findings indicated that digital literacy skills had a positive and significant relationship with off-campus teaching at selected university libraries in Kenya. The study concluded that digital literacy skills had a positive and significant relationship with off-campus teaching at selected university libraries in Kenya. The study recommended library management to strengthen digital literacy skills. In particular, the library management should focus on the following critical skills: literacy searching skills, citing and referencing skills, literature synthesizing skills, and scholarly writing skills. The study makes significant contribution to policy, theory and practice in the field of information science